POLA PENGGUNAAN INTERNET OLEH KALANGAN REMAJA DI KABUPATEN SEMARANG - Ester Krisnawati (Universitas Kristen Satya Wacana, 2015)
The easiness of internet access facilities and the more sophisticated the facilities offered by the internet in the era of Information and Communication Technology today was accompanied by the emergence of phenomena that shows high interests in youth to use the Internet. of this phenomenon, the researchers wanted to see how the patterns of Internet usage by teenagers in Semarang District. This research uses quantitative methods to conduct surveys using questionnaires distributed to respondents in various regions of the Semarang District. The number of samples representing the respondent populations studied were 464 respondents. From this research it is known that more teenagers choose the Internet to search for information, in addition to the media most frequently used to access the internet is mobile. information most often sought by teenagers on the internet are looking for information about hobbies and entertainment. Keywords : teenagers, internet, information